2019
DOI: 10.1111/hsc.12865
|View full text |Cite
|
Sign up to set email alerts
|

Views on the use of the term ‘elder orphans’: A qualitative study

Abstract: Older adults living alone in the community with no immediate family network or support are referred in the literature as ‘elder orphans’. The grey literature has a growing emphasis on the importance of supporting this vulnerable group, particularly with health and social care. However, there is a dearth of empirical research on ‘elder orphans’, and definitions remained semantically complicated and unknown to the public, healthcare professionals and those being referred as elder orphans. This research explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The greater physical vulnerability of older females related to factors such as low education and remuneration, loneliness, social isolation and family distancing is described in the literature (21,23) . Support from family care, proximity of people with the maintenance of social networks and access to information can provide a better maintenance of functional capacities, as well as providing a greater guarantee of support in the face of physical, psychological and social needs (24)(25) .…”
Section: Discussionmentioning
confidence: 99%
“…The greater physical vulnerability of older females related to factors such as low education and remuneration, loneliness, social isolation and family distancing is described in the literature (21,23) . Support from family care, proximity of people with the maintenance of social networks and access to information can provide a better maintenance of functional capacities, as well as providing a greater guarantee of support in the face of physical, psychological and social needs (24)(25) .…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study exploring the views of elder orphans on the use of this term, Montayre and colleagues found that participants, while initially ambivalent, later identified with the term and acknowledged its utility to alert clinicians of their circumstances and direct services appropriately. 21 It is important to note that participants did not endorse the term's use publicly, but within medical contexts. Some participants expressed embarrassment or dislike of the term, aligning with popular media contesting its use as infantilizing or stigmatizing.…”
Section: Critical Considerations and Conflicting Perspectivesmentioning
confidence: 99%
“…Teaster et al (2006) define a vulnerable adult as "a person who is either being mistreated or in danger of mistreatment and who, due to age and/or disability, is unable to protect." However, the definition of a vulnerable adult varies by state (Montayre et al, 2020). Some states place age restrictions with a demarcation between a vulnerable adult and a vulnerable elder.…”
Section: The Impetus: Rule 608mentioning
confidence: 99%